Interactive Shared Book Reading with a Narrative and an Informational Book: The effect of genre on parent-child reading - Baldwin, Charles G.; Morrow, Lesley M. (Preschool and Primary Education, 2019)
Introduction: Previous studies indicate the dominance of narrative fiction in shared book reading. Theory and research suggests this may contribute to reading difficulties. Purpose of the Study: This study contrasted the impact of two genres on shared book reading based on factors known to maximize children’s literacy development. It also examined the participants’ perspectives regarding their interactive reading behaviors. Methods: Eight parent-child dyads, with children four- and five-years-old, read a non-narrative informational book and a narrative fictional book. The study controlled for the books’ reading levels, Rockets and Spaceships (Guided Reading K, Lexile 520) and A Penguin Pup for Pinkerton (Guided Reading K, Lexile 510). Results: Analysis showed that informational book features such as captions, predictable text, and a glossary supported interactive reading behaviors. Children engaged more with concrete, factual concepts, and answered and asked more questions with the informational book. Implications and Conclusions: Analysis showed that the non-narrative informational text encouraged more children’s interactive reading behaviors known to develop emergent literacy skills. The informational text was more engaging for children because of 1) book features/characteristics, and 2) the information presented. Parents were generally unaware of the benefits of reading multiple genres to their children.